The Influence of Work Discipline Systems on Perceived Accident Risk and Unsafe Behaviors in Ship Loading and Unloading Operations - Asteria Narulita Pramana; Muh. Fauji; Sahrul Sahrul (Jurnal Kesehatan Komunitas Indonesia, 2026)
Work discipline plays a vital role in preventing accidents during coal loading and unloading activities on ships. This study aims to analyze the influence of the disciplinary system on the risk of ship-loading and unloading accidents at PT SMD in Semarang. The method used was quantitative research with a cross-sectional survey design. Given that the total population of truck drivers at PT SMD was exactly 55, we employed total population sampling, examining all available workers. Data collection used a Likert scale questionnaire. Statistical tests included validity, reliability, normality (One-Sample Kolmogorov-Smirnov), and simple linear regression. All 10 items of the discipline instrument were declared valid (r > 0.3) with a Cronbach's alpha of 0.927 (very high). Of the 10 items of the loading and unloading instrument, 9 were valid and had a reliability of 0.874 (high). The normality test showed Asymp. Sig. = 0.200 (> 0.05), meeting the assumption of a normal distribution. The ANOVA test results showed Sig. = 0.000 (< 0.05), indicating the regression model is significant. The discipline system significantly influences the risk of ship loading and unloading accidents; the higher the level of worker discipline, the lower the risk of such accidents.